Treatment-refractory obsessive compulsive disorder - Atmaca, Murad (Pergamon-Elsevier Science Ltd, 2016)
Obsessive compulsive disorder (OCD) is a chronic and debilitating disorder. As can be seen in other psychiatric disorders, refractoriness to treatment is an important problem for patients with OCD. OCD is a chronic disorder like collagen tissue disorders, with symptoms tending to wax and wane but rarely remitting spontaneously through the course of the disorder. An important part of OCD patients respond to serotonin reuptake inhibitors alone or in combination with other medications, and cognitive behavior therapy. However, up to 30%-40% of patients do not respond to the available treatment modalities. The present paper tried to review the current state of knowledge on definition, clinical aspects, etiopathogenesis, and treatment strategies of patients with refractory OCD. (C) 2015 Published by Elsevier Inc.
Keywords: OCD; Refractory; Treatment; Clinical aspects